Analisis Komoditas Unggulan Tanaman Pangan dan Kinerja Terhadap Pembangunan Pertanian di Kabupaten Lampung Barat - Hernita Astuti (Balitbangda Provinsi Lampung, 2015)
Agricultural development policy that made great performance or contribution is expected to stimulate economic development. The problems identification of this study are what kinds of leading commodities of food crops at Lampung Barat regency. The purpose of this study to determine the leading commodities of food crops at Lampung Barat regency and how food crops commodities contribution at Lampung Barat Regency. Basic methods used in this study is descriptive analysis. This study used secondary data in time series form for five years starting from 2009 until 2013 that includes : 1) Production value data of food crops at Lampung Barat regency the year 2009 until 2013, and 2) Production value data of food crops at Lampung Province the year 2009 until 2013. The analysis that calculated including location quotient (LC), dynamic location quotient (DLQ) and shift share (S-S) method. From the results of research obtained 1) the leading commodities of food crops that potential to develop as economic drivers at Lampung Barat regency such as sweet potato and peanut, where as this commodity has competitive character, growing fast and surplus, and 2) Food crops commodities at Lampung Barat regency that can still be expected to be the production base at the future is sweet potato, peanut, soybean and mungbeans. Besides food crops like rice, corn and cassava can’t be expected to be the production base at the future.